Angiotensin-converting enzyme 2: angel or evil? - Gironacci, Mariela M. (2021)
Angiotensin converting enzyme 2 (ACE2) is a key element of the protective arm of the reninangiotensin system (RAS). ACE2 acts to oppose the actions of angiotensin (Ang) II by generating Ang-(1–7) to reduce inflammation and fibrosis and mitigate end organ damage. ACE2 also acts as the receptor for severe acute respiratory syndrome (SARS)-coronavirus (CoV)-2 to gain entry into human cells. SARS-CoV-2 is the etiological agent that causes coronavirus disease 2019 (COVID-19). The COVID-19 pandemic is associated with significant morbidity and mortality throughout the world, predominantly due to lung and cardiovascular injury. The present review is focused on ACE2, as a protective component of the RAS and as the receptor for SARS-CoV2.